Resting cardiopulmonary function in paralympic athletes with cervical spinal cord injury - West, C. R.; Campbell, I. G.; Shave, R. E.; Romer, L. M. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The purposes of this study were to describe resting cardiopulmonary function in highly trained athletes with cervical spinal cord injury (SCI) and to compare the data with able-bodied (AB) control subjects. Methods: Twelve Paralympic wheelchair rugby players with cervical SCI (injury level = C5-C7) and 12 AB controls matched for age, stature, and body mass were assessed for pulmonary function using spirometry, body plethysmography, and maximal inspiratory and expiratory mouth pressures; diaphragm function using magnetic stimulation of the phrenic nerves; and cardiac function using transthoracic echocardiography. Results: Total lung capacity, vital capacity, inspiratory reserve volume, and expiratory reserve volume were lower in SCI compared with AB (P G 0.01), whereas residual volume was elevated in SCI (P = 0.022). Airway resistance and maximal inspiratory mouth pressure were not different between groups (P 9 0.41), whereas maximal expiratory mouth pressure, maximal transdiaphragmatic pressure, and twitch transdiaphragmatic pressure were lower in SCI (P G 0.01). Percent predicted total lung capacity was significantly correlated with maximal transdiaphragmatic pressure in SCI (r = 0.74), suggesting that the pulmonary restriction was a result of diaphragm weakness. Left ventricular mass, ejection fraction, stroke volume,and cardiac output were lower in SCI (P G 0.04), but early and late filling velocities during diastole were not different between groups (P 9 0.05). Conclusions: Highly trained athletes with cervical SCI exhibit a restrictive pulmonary defect, weakness of the expiratoryand diaphragm muscles, atrophy of the heart, and reduced systolic cardiac function.